2012
DOI: 10.1371/journal.pone.0042314
|View full text |Cite
|
Sign up to set email alerts
|

Neuroligin-1 Loss Is Associated with Reduced Tenacity of Excitatory Synapses

Abstract: Neuroligins (Nlgns) are postsynaptic, integral membrane cell adhesion molecules that play important roles in the formation, validation, and maturation of synapses in the mammalian central nervous system. Given their prominent roles in the life cycle of synapses, it might be expected that the loss of neuroligin family members would affect the stability of synaptic organization, and ultimately, affect the tenacity and persistence of individual synaptic junctions. Here we examined whether and to what extent the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 76 publications
6
29
0
Order By: Relevance
“…In comparison to metabolic half-lives, residency half-lives are orders of magnitude shorter (Synapsin-1: ∼1 h vs. ∼4.9 days; Bassoon: ∼3 h vs. ∼2.6d, Munc-13–1: ∼1 h vs. ∼1.3d; PSD-95: ∼3.3 h vs. ∼3.7d; residency vs. metabolic turnover half-lives, respectively [7], [71], [72], [73]); these differences become even more apparent when considering the short residency times of integral membrane proteins (e.g. [22], [24], [74]).…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to metabolic half-lives, residency half-lives are orders of magnitude shorter (Synapsin-1: ∼1 h vs. ∼4.9 days; Bassoon: ∼3 h vs. ∼2.6d, Munc-13–1: ∼1 h vs. ∼1.3d; PSD-95: ∼3.3 h vs. ∼3.7d; residency vs. metabolic turnover half-lives, respectively [7], [71], [72], [73]); these differences become even more apparent when considering the short residency times of integral membrane proteins (e.g. [22], [24], [74]).…”
Section: Discussionmentioning
confidence: 99%
“…NLGNs are present postsynaptically and form a trans-synaptic signal transduction complex with presynaptic neurexins; they participate in the recruitment of synaptic proteins, and thereby play an important role in the maturation and activity-dependent regulation of synaptic contacts [3], [4], [6], [9][11]. Previous immunocytochemical experiments localized NLGN2 exclusively to GABAergic and a small subset of glycinergic synapses [13], [14].…”
Section: Discussionmentioning
confidence: 99%
“…Both NLGNs and neurexins recruit proteins that are involved in synaptic communication and are able to induce pre- or postsynaptic specializations [3][5]. Experiments with NLGN-knockout (KO) mice demonstrated that NLGNs play an important role in the maturation and proper function of synapses [6], [7] and appear to be dynamically regulated and therefore contribute to the activity dependent stabilization/destabilization of synapses [8][11].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism linking LTP to synaptic stabilization, and LTD to destabilization, is likely to involve several processes. Synaptic tenacity is known to be affected by trans-synaptic proteins 11 such as Neuroligin-1 and SynCAM-1 (Zeidan and Ziv, 2012;Körber and Stein, 2016), PSD-95 (De Roo et al, 2008;Cane et al, 2014), ubiquitin protein ligase E3A (Kim et al, 2016), ensheathment of the synapse by astrocyte processes (Bernardinelli et al, 2014) and many other local factors. It may be a combination of local physical changes and distributed network effects, such as the recurrent reactivation of a specific circuit (Wei and Koulakov, 2014;Novitskaya et al, 2016), which makes once potentiated synapses robust against depression ( Figure 5B) and pruning ( Figure 3E).…”
Section: Discussionmentioning
confidence: 99%